Analysis and implementation of transformerless LCL resonant power supply for ozone generation - Salam, Z.; Amjad, M.; Facta, M.; Mekhilef, Saad (Institute of Electrical and Electronics Engineers, 2013)
This paper describes the analysis and design of an LCL resonant power supply for ozone generation. The main advantage of the proposed topology is the absence of high-voltage transformer; the high voltage gain is achievable by means of double-resonance phenomena. Furthermore, the bandwidth is wider than the ordinary LC and its phase difference is constant over specific frequency range; as a result, an open-loop operation can be implemented. The complete analysis and design procedure of the power supply is presented. The design procedure is verified by implementing the power supply to drive a dielectric barrier discharge prototype ozone chamber. The hardware results are found to be in close agreement with simulation and thus justify the validity of the design procedures. The proposed circuit is suitable for portable ozone power supply fed by low-voltage source such as battery or photovoltaic module.